A novel approach to the treatment of type B aortic dissection and common iliac artery aneurysms in a patient necessitating redo renal transplantation - Khabaz, Kameel; Subramanian, Tanvi; Milner, Ross (International Surgery Journal, 2023)
In patients with end-stage renal disease (ESRD), treatment of common iliac artery (CIA) aneurysm disease necessitates safe operative repair while simultaneously maintaining candidacy for future renal transplant. We present the case of a patient with a type B aortic dissection and aorto-biiliac aneurysmal degeneration who has a previously failed right kidney transplant. Initial operative planning was approached with three goals: 1) endovascular repair as possible; 2) minimize paraplegia risk; 3) maintain renal transplant candidacy. As such, a three-stage operation was planned. Endovascular repair of the R CIA aneurysm was followed by thoracic endovascular aortic repair (TEVAR). The third stage, repair of AAA and left CIA aneurysm, was performed open using an aorto-biiliac graft with a surgically modified prosthetic bypass to preserve the left internal iliac artery to reduce paraplegia risk and the left external iliac artery (EIA) for future kidney transplantation. This novel technique successfully allowed for surgical repair of the Type B aortic dissection and the CIA aneurysms, while maintaining the patient’s future redo transplant candidacy with minimal paraplegia risk.